Implementasi Media Pembelajaran SMPN 8 Palangka Raya Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas VII - Lisdayanti Tinambunan; Jesica Carolina; Royasefa Ketrin Suek; Nafaya Yesilia; Triani Cahya Ningsih; Fitri Fitri; Matius Timan Herdi Ginting (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
This research focuses on the implementation of conventional and digital learning media in Christian Religious Education and Character Education at SMP Negeri 8 Palangkaraya. The study aims to analyze the effectiveness of these media in enhancing student understanding and engagement. A quantitative experimental design was employed, involving 106 seventh-grade students divided into groups using different media: educational snake and ladder games for conventional media and interactive PowerPoint presentations for digital media. Data were collected through observations and Likert-scale questionnaires. The findings indicate that both media effectively foster a lively learning atmosphere, with students showing high enthusiasm and participation. The conventional media was particularly beneficial for active learners, while digital media catered to visual learners. The implications suggest that varied media use can enhance teaching quality and accommodate diverse learning styles, making learning more engaging and meaningful.